Perilaku Keuangan Rumah Tangga Muslim: Peran Religiusitas dan Literasi Keuangan dalam Konteks Sosial Ekonomi: Indonesia - Hanafir Rifqi, Lathif; Zahrotun Nihayah, Ana; Mujibatun, Siti; Huda, Nur (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2026)
Money is very important for economic actors, including households. Both poor household economic conditions can be seen from household orders in managing finances. This way of managing finances will provoke household financial behavior. Many divorces in Indonesia are caused by economic factors. Behind these economic factors, it is suspected that there is bad financial behavior from household partners. Therefore, it is necessary to look for various factors that shape household financial behavior. The search and analysis was carried out philosophically normatively using a literature approach. Various previous studies regarding the factors that shape financial behavior are summarized and examined empirically normatively. The results obtained six factors forming household financial behavior. These factors are a) religiosity, b) financial literacy, c) age, d) formal education, e) income, and f) number of family dependents.